2020
DOI: 10.5005/jp-journals-10005-1853
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Mineral Trioxide Aggregate and Biodentine as Apical Barriers in Immature Permanent Teeth: A Microbiological Study

Abstract: Aim To compare the bacterial leakage of mineral trioxide aggregate (MTA) and biodentine when used as an apical plug in immature permanent teeth. Materials and methods It was a randomized double-blind in vitro study. A total of 60 teeth were divided into 2 groups of MTA and biodentine, which were further divided into 2 subgroups ( n = 30) each based on the apical plug thickness of 2 and 4 mm. The teeth were cleaned an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 34 publications
0
6
0
2
Order By: Relevance
“…MTA functions similarly in terms of furcal sealing and antibacterial efficacy in both the gray and white forms [15] (Figure 4). While the white variant is linked to the formation of keratinocytes and cementoblasts, the gray form exhibits more favorable behavior for odontoblast development in vitro.…”
Section: Discussionmentioning
confidence: 93%
“…MTA functions similarly in terms of furcal sealing and antibacterial efficacy in both the gray and white forms [15] (Figure 4). While the white variant is linked to the formation of keratinocytes and cementoblasts, the gray form exhibits more favorable behavior for odontoblast development in vitro.…”
Section: Discussionmentioning
confidence: 93%
“…The application of other bioceramics as apical barriers has also been reported. Biodentine as an apical barrier is better at preventing bacterial leakage than MTA in vitro [ 78 , 79 ]. Apical barrier techniques using MTA, Biodentine, and CEM increase the fracture resistance of immature teeth [ 80 , 81 ].…”
Section: Clinical Applications In Endodonticsmentioning
confidence: 99%
“…The major disadvantage of using calcium hydroxide for apexification is that it requires a long term followup, in contrast Biodentine allows for a single visit apexification procedures and this barrier will prevent the penetration of toxins and bacteria from the root canal as well as this barrier allows for compaction of root filling material [20] . Abbas A et al, evaluated the efficacy of MTA and Biodentine as apical barriers in immature permanent Teeth and they found that the sealing capabilities was similar for both MTA and Biodentine irrespective of its thickness and better seal was created when Biodentine was used in increased thickness [21] .…”
Section: Apexificationmentioning
confidence: 99%